Confocal microscopy for process monitoring and wide-area height determination of vertically-aligned carbon nanotube forests - Piwko, Markus; Althues, Holger; Schumm, Benjamin; Kaskel, Stefan (Coatings, 2015)
Confocal microscopy is introduced as a new and generally applicable method for the characterization of the vertically-aligned carbon nanotubes (VACNT) forest height. With this technique process control is significantly intensified. The topography of the substrate and VACNT can be mapped with a height resolution down to 15 nm. The advantages of confocal microscopy, compared to scanning electron microscopy (SEM), are demonstrated by investigating the growth kinetics of VACNT using Al 2 O 3 buffer layers with varying thicknesses. A process optimization using confocal microscopy for fast VACNT forest height evaluation is presented.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Chemical vapor deposition; Confocal microscopy; Forest height characterization; Optical imaging; Vertically aligned carbon nanotubes